2021
DOI: 10.1021/acssynbio.0c00562
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Biomanufacturing of Small Molecules in the Mammalian Gut by Probiotic Saccharomyces boulardii

Abstract: Saccharomyces boulardii is a probiotic yeast that exhibits rapid growth at 37 °C, is easy to transform, and can produce therapeutic proteins in the gut. To establish its ability to produce small molecules encoded by multigene pathways, we measured the amount and variance in protein expression enabled by promoters, terminators, selective markers, and copy number control elements. We next demonstrated efficient (>95%) CRISPR-mediated genome editing in this strain, allowing us to probe engineered gene expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(97 citation statements)
references
References 83 publications
2
94
1
Order By: Relevance
“…β-Carotene concentration can be between 680 and 2,255 nM in circulation depending on whether it is consumed as a pure compound or within the foods (54,56). We recently reported that engineered S. boulardii synthesized high doses of β-carotene in the colon of mice, and the intake of such engineered probiotics may result in an even higher β-carotene concentration in the gut (57). Altogether, the dosage of β-carotene used in this study is within physiological relevance and can be achieved by humans.…”
Section: Discussionmentioning
confidence: 99%
“…β-Carotene concentration can be between 680 and 2,255 nM in circulation depending on whether it is consumed as a pure compound or within the foods (54,56). We recently reported that engineered S. boulardii synthesized high doses of β-carotene in the colon of mice, and the intake of such engineered probiotics may result in an even higher β-carotene concentration in the gut (57). Altogether, the dosage of β-carotene used in this study is within physiological relevance and can be achieved by humans.…”
Section: Discussionmentioning
confidence: 99%
“…S2A-D) compared to S. cerevisiae. Indeed, from understanding the regulatory mechanisms of the mating pathway, and taking advantage of S. boulardii's growth, survival, and residence time in the gastrointestinal tract as compared to S. cerevisiae 36 , we envision that probiotic S. boulardii can now be engineered to dynamically respond to disease markers for timely and accurate secretion of therapeutic compounds, and as such adds an important capability to its already established therapeutic potential. Extending from this we furthermore foresee this study to foster the development of growth-based high-throughput screens of hGPCR-mediated chemotropism within environmental engineering, MAPK pathway signaling, drug discovery for therapeutic purposes, and enzyme optimization for metabolic engineering and biotechnology.…”
Section: Discussionmentioning
confidence: 99%
“…pDAM123 was made by assembling fragments from gDAM15 (α-leader secretion signal and P-factor) ampli ed with DAM76+DAM78, P TEF1 ampli ed with 1564+1565, and T CYC1 ampli ed with DAM80+DAM81, into pCfB2899. Plasmid pJV452 was constructed by Gibson (NEB) assembly of pEDJ400 linearized with oligos JV498+JV499, which excluded the 2μ element, and CEN/ARS from plasmid DD118 36 ampli ed with oligos JV500+JV501. Plasmid pDAM194 containing P FUS1 -yEGFP-T FUS1 was made by ampli cation of gDNA from strain CPK16 with oligos JV502+JV503, which was then assembled into plasmid pJV452.…”
Section: Molecular Cloningmentioning
confidence: 99%
See 1 more Smart Citation
“…S. boulardii may also be able to deliver other therapeutics, including bacteriocin, cytokines, peptides, and small molecular drugs. 120–123 In order to improve the yield of target cargoes, the components of the gene cassettes, such as signal peptides, promotors/terminators, selection markers, etc., and maintenance of the exogenous gene of interests as plasmids or chromosomal integration have been modified in those studies. Among them, Chen et al and Liu et al have demonstrated the in vivo activity of the yeast-secreted heterologous proteins after passing through animal GI tract.…”
Section: Recombinant Live Biotherapeutic Productsmentioning
confidence: 99%